Edible Insect Meals as Bioactive Ingredients in Sustainable Snack Bars - Francesca Coppola; Silvia Jane Lombardi; Patrizio Tremonte (Foods)
Insect metabolites are known for their preservative potential, but the time-consuming and unsustainable extraction process compromises their transferability. This study aimed to identify user-friendly solutions based on the use of insect meals that could improve microbiological safety as well as consumer acceptability. In this regard, the antimicrobial activity of Alphitobius diaperinus and Tenebrio molitor meals against surrogate strains of Gram-positive (Listeria monocytogenes) and Gram-negative (Escherichia coli) pathogenic bacteria and mycotoxin-producing fungi (Penicillium expansum) was evaluated. Minimum inhibitory concentration values of between 3.12 mg/mL vs. Listeria innocua and 12.50 mg/mL vs. Escherichia coli were found. Based on this finding, a model food was developed also considering consumer acceptance. Statistical analysis of food preferences showed that nutritional and sustainability claims were the independent variables of greatest interest. Therefore, waste or by-products from other food chains were selected as co-ingredients for sustainability, nutritional, and sensory claims. Analysis of the chemical composition showed that the insect bar-style snack qualifies as a “high-protein” food, as protein provides more than 20% of the energy value. Based on the moisture (30%) and water activity (0.77) values, the bar could be classified as an intermediate-moisture food. The challenge test showed that the insect meal prevented the proliferation of intentionally added undesirable microorganisms. Conclusively, the findings complement the knowledge on the antimicrobial activities of insect meals, offering new possibilities for their use as natural preservative ingredients with nutritionally relevant properties.